2015
DOI: 10.1073/pnas.1420101112
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude of the actomyosin power stroke depends strongly on the isoform of the myosin essential light chain

Abstract: We have used time-resolved fluorescence resonance energy transfer (TR-FRET) to determine the role of myosin essential light chains (ELCs) in structural transitions within the actomyosin complex. Skeletal muscle myosins have two ELC isoforms, A1 and A2, which differ by an additional 40-45 residues at the N terminus of A1, and subfragment 1 (S1) containing A1 (S1A1) has higher catalytic efficiency and higher affinity for actin than S1A2. ELC's location at the junction between the catalytic and light-chain domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 48 publications
6
48
0
Order By: Relevance
“…For TR-FRET measurements, we used time-correlated single-photon counting (41) or direct waveform recording, as described previously (29,30). Global multiexponential analysis of the TR-FRET data was used to test a series of structural models, as described extensively elsewhere (30,41) This mode of analysis resolves both binding and structural information from TR-FRET data.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For TR-FRET measurements, we used time-correlated single-photon counting (41) or direct waveform recording, as described previously (29,30). Global multiexponential analysis of the TR-FRET data was used to test a series of structural models, as described extensively elsewhere (30,41) This mode of analysis resolves both binding and structural information from TR-FRET data.…”
Section: Methodsmentioning
confidence: 99%
“…Global multiexponential analysis of the TR-FRET data was used to test a series of structural models, as described extensively elsewhere (30,41) This mode of analysis resolves both binding and structural information from TR-FRET data. SR membranes labeled with D-FKBP were incubated with 200 M S100A1 for 2 h at 22°C before a 30-min incubation at 22°C with 800 nM A-CaM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work showed that when myosin binds to actin, the NTE of fast skeletal or cardiac ELC is in close proximity to actin ( Fig. 1) (4,5). N-terminal amino acids of NTE, specifically the first four amino acids (APKK), are highly conserved among skeletal and cardiac muscles and also across species (6).…”
mentioning
confidence: 99%
“…These positively charged lysine residues interact with the negatively charged C terminus glutamates of actin (7). The actin-NTE interaction is functionally relevant, because myosin isoforms having NTEs show higher catalytic efficiency and slower motility on actin (3,8,9).Recent studies from our laboratory have explored the structural basis of ELC-mediated modulation of the actin-myosin interaction (4,5,10). Time-resolved FRET (TR-FRET), using a donor on actin and an acceptor on the A1 NTE of skeletal myosin subfragment 1 (S1), showed that the NTE plays an important role modulating myosin's force-producing powerstroke (4).…”
mentioning
confidence: 99%